2009
DOI: 10.1007/s11250-009-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing production of hygienic raw milk by small scale dairy producers in selected areas of the Jaffna district, Sri Lanka

Abstract: The objective of the study was to investigate the influence of dairy cow management techniques and milking methods on hygienic quality of raw milk. Total Bacterial Count (TBC) and Total Coliform Colonies (TCC) were studied to determine the effects. Investigations were carried out in fifty dairy farms from August 2007 to December 2007. The mean TBC and TCC for the herds with comparatively good and poor management practices were 0.9 x 10(5) cfu/ml and 0.2 x 10(3)/ml and 99 x 10(5) cfu/ml and >180 x 10(3)/ml, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
7
2
1
Order By: Relevance
“…Some countries have no milk microbial limits like India (Lingathurai and Vellathurai, 2010). However, the main challenge of the standards regulatory bodies in ensuring production, distribution, and consumption of good quality and safe milk is the lack of resources in terms of personnel and equipment (Fuquay et al, 2011;Vairamuthu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some countries have no milk microbial limits like India (Lingathurai and Vellathurai, 2010). However, the main challenge of the standards regulatory bodies in ensuring production, distribution, and consumption of good quality and safe milk is the lack of resources in terms of personnel and equipment (Fuquay et al, 2011;Vairamuthu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mollicutes are very susceptible to adverse environmental conditions and respond by cell lysis to osmotic shock caused by detergents (Chambaud et al 1999). However, cleaning the milking room with only water or with an inadequate amount of detergent is insufficient to eliminate the agent and is a risk factor in the maintenance of microorganisms in the ambient environment (Vairamuthu et al 2010). It also increases the risk of their dissemination by the hands of the milker (Al-Momani et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A higher total viable count and Coliform count have been recorded even in bulk containers (Ranasinghe et al, 2017). Vairamuthu et al (2010) stated that milk quality of Jaffna district has been drastically affected by the following practices during milking; washing the udder and hands with only water without a detergent, wiping the udder after washing only using hand, and the milking of infected and healthy cows at the same time. They have also found that the total aerobic bacteria and 5 3 coliform counts were 22 x 10 and 47 x 10 CFU, respectively and these values are higher than the acceptable levels.…”
Section: Quality Of Milk In Sri Lankamentioning
confidence: 99%